Studies on the Pathogenesis of the Generalized Shwartzman Reaction - Rodríguez-Erdmann, F; Naimi, S (Thrombosis and Haemostasis, 1967)
Autoprothrombin-C (factor Xa) was given intravenously to rabbits whose RES had been previously blocked with thorotrast. The coagulo-analytical results as well as the morphological changes resemble those of the classical generalized Shwartzman reaction (gSr) produced by properly spaced doses of Gram-negative endotoxin. The results are discussed in the light of the literature.